Does Acupuncture Protect Dopamine Neurons in Parkinson's Disease Rodent Model?: A Systematic Review and Meta-Analysis - Ko, Jade Heejae; Lee, Hyangsook; Kim, Seung-Nam; Park, Hi-Joon (Frontiers in Aging Neuroscience, 2019)
Background Acupuncture has been reported to have significant effects in not only alleviating motor function, but also rescuing dopamine neuron deficit of Parkinson’s disease (PD) rodent model. However, systemic analysis of these beneficial effects has yet to be evaluated. Objective To evaluate the neuroprotective effect of acupuncture in animal models of PD Methods A literature search was conducted using PubMed, MEDLINE, EMBASE, CNKI, RISS, and JJSAM to collect studies that investigated effects of acupuncture on PD. Study quality of each included article was evaluated based on the 10-item checklist modified from CAMARADES. The software RevMan 5.3 was used for the meta-analysis. Results 42 studies were included and the included studies scored between 2 and 7 points, with a mean of 4.6. Outcome measures include TH level and dopamine content. The result of meta-analysis showed significance of acupuncture for increasing both TH level (33.97, 95% CI: 33.15 ~ 34.79; p < 0.00001) and dopamine content (4.23, 95% CI: 3.53 ~ 4.92; p < 0.00001) compared with the PD control groups. In addition, motor dysfunctions showed in PD animal were also mitigated as a result of acupuncture treatment. Conclusions While there are limitations in number and quality of included studies, this study suggests that acupuncture shows the effect of dopamine neuron protection in PD rodent models.